Production potential of newly released potato (Solanum tuberosum L.) cultivars under different nitrogen levels - Das, SK; Banerjee, H; Chakraborty, A; Sarkar, A (SAARC Journal of Agriculture, 2016)
Field experiments were conducted during rabi seasons of 2011-12, 2012-13, 2013-14 and 2014-15 at C-unit research farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, Nadia, West Bengal, India to study the effects of different levels of nitrogen on the productivity of newly released potato (Solanum tuberosum L.) cultivars under lower Gangetic plains of West Bengal. The experiment was laid out in a factorial randomized block design with four replications having ten treatment combinations viz. two levels of newly released cultivars (V1 - Kufri Himalini and V2 - Kufri Shailja) as factor A and five levels of nitrogen (N0 -0 kg ha-1, N75 -75 kg ha-1, N150 -150 kg ha-1 N225-225 kg ha-1 N300 -300 kg ha-1) as factor B. Experimental results revealed that highest tuber yield (25.77 t ha-1) was recorded with Kufri Himalini receiving 300 kg N ha-1 followed by 24.64 t ha-1 and 23.64 t ha-1 with 225 kg N ha-1 and 150 kg N ha-1 respectively which is quite higher than the state average of 22.02 t ha-1 obtained from the state recommended dose of 200 kg N ha-1, 150 P2O5 ha-1 and150 K2O ha-1. Thus recently released variety Kufri Himalini, having moderate resistance against late blight, which is a serious problem in the state at present can be a better option for the farmers of the state to raise the potato production. Kufri Himalini produced significantly higher (14.1%) total tuber yield over Kufri Shailja and it was found to be more acceptable to the farmers in terms of production of marketable tuber (> 75 g grade). Grade wise tuber yield of potato was significantly influenced by N levels. Irrespective of cultivars application of 300 kg N ha-1 along with recommended dose of P and K recorded the highest total potato tuber yield (23.55 t ha-1) which was found statistically at par with the application of 225 kg N ha-1 and 150 kg N ha-1. Nitrogen fertilization improved the tuber yield of potato by 49.5 to 82.1% over control. Kufri Himalini was more responsive to fertilizer nitrogen than Kufri Shailja as it recorded higher agronomic efficiency (AEN), apparent recovery (REN) and physiological efficiency (PEN) at all nitrogen levels. There was a positive balance of nitrogen found in all treatments. Net gain of soil N was highest with Kufri Himalini receiving 150 kg N ha-1. Kufri Himalini gave highest net return with 300 kg N ha-1. SAARC J. Agri., 13(2): 121-130 (2015)